Validity of Child Friendly School Management Model Based on Minangkabau Natural Cultural Values - Irman; Dasman Lanin; Mudjiran; Maria Montessori (International Journal on Integrated Education, 2022)
The implementation of the school-based management model (SBM) has not been able to meet the demands of child-friendly school indicators, the average implementation of child-friendly school indicators in SDs in Tanah Datar district in 2019 was 34.38% which can be interpreted as not being implemented properly, library space is not adequate, do not have labor, the UKS room is not adequate, the school canteen is not healthy, the worship space is still lacking, the toilets for students are not adequate. The study aimed to develop the validity of a valid child-friendly school management model based on Minangkabau natural cultural values. The method used is research and development (R&D), the model used is ADDIE. The results of the study on the child-friendly school management model based on the Minangkabau natural culture values from the product validity test based on the validation of the model instrument obtained an average score of 3.67 which was declared "Valid" and while the results of the validation of the Mesra-Sisnibam model book get an average of 3.93 or are in the "valid" category, thus the validation of the child-friendly school management model based on Minangkabau natural cultural values is very suitable for use in the learning process in SDs.